Potential environmental and population health impacts of local urban food systems under climate change: a life cycle analysis case study of lettuce and chicken - Hall, Gillian; Rothwell, Alison; Grant, Tim; Isaacs, Bronwyn; Ford, Laura; Dixon, Jane; Kirk, Martyn; Friel, Sharon (BioMed Central, 2014)
Background: Climate change is expected to have an impact on food production, processing and transport systems. While food systems have become globalized in recent decades, interest has re-emerged for local production and consumption to contribute to sustainable and secure food systems in an era of increasing urbanization and climate change. To explore environmental health issues related to the production of local food in an urban setting, a life cycle analysis screening study of two food commodities, chicken meat and lettuce, produced at industrial and civic scales was conducted in Sydney, Australia, as well as interviews with consumers and producers to explore their potential motivation to change. Methods: Determination of environmental impacts was performed using life cycle assessment (LCA) of two civic and one industrial scale producer for each commodity using SimaPro version 7.3.3. Impacts of global warming potential (GWP), land use and water use from the production of these commodities are reported. With a view to producing holistic insights to sustainable practices in Sydney, interviews with producers and consumers were undertaken to assess sociocultural outcomes including views on environmental food sustainability and other motivators of behavioral change. Results: Local industrial production of chicken meat was found to have a lower carbon footprint than small scale civic production. Small scale civic production of lettuce had a similar carbon footprint to local industrial production. Other environmental health benefits and risks varied across the production scales. Environmental sustainability was not generally a key concern of producers or consumers. Conclusions: Action can be taken to retain and promote food production in urban settings as a future means of assisting food security. The scale of production can be an important variable in assessing the environmental health impacts of food production in an urban setting. Currently neither producers nor consumers appear motivated to change practices to promote environmental sustainability.
Keywords: Urbanization; Scale of food production; Carbon footprint; Life cycle assessment